SERGEI RACHMANINOFF’S PIANO CONCERTO NO. 4, OP. 40: IMPLICATIONS OF THE ARC SHAPE IN THE FORMAL STRUCTURE AND IN RACHMANINOFF’S INTERPRETATIVE CONCEPTION - FODOR, Georgiana (Studia Universitatis Babes-Bolyai Musica, 2017)
The purpose of this study is to illustrate the relation between the elaboration of form within the compositional process and its implications in the interpretative act. I have chosen to discuss Sergei Rachmaninoff’s Concerto No. 4 in G minor Op. 40 for piano and orchestra, one of his most significant late works, given the evolution of his musical language. For the performance analysis I relied on Rachmaninoff’s own recording of this work. I have particularly focused on the importance of the arc shape (prominent feature and major Tchaikovskian heritage in Rachmaninoff’s work), an organising principle which impresses not only the dynamic and metric physiognomy of the work, but also the musical thought of the performer.